Modified output and metalanguage during conversational interaction: A qualitative look at interactional feedback - Canals, Laia (Studies in Second Language Learning and Teaching, 2023)
The present study draws on earlier research on learner-learner dyadic interactions in an e-tandem virtual exchange and examines negotiation of meaning episodes based on the qualitative data. These data come from learner-learner interactions during oral tasks carried out using a video conferencing tool. The aim is to unveil the interactional patterns that emerge during negotiation of meaning episodes which have been deemed beneficial for L2 development, particularly those which offer opportunities for modified output to occur (Gurzynski-Weiss & Baralt, 2015; Long, 1996; Pica, 1994; Schmidt, 1990). The results highlight the role that metalinguistic information plays in scaffolding the process of negotiation of meaning and emphasize the benefits of e-tandem exchanges where learners alternate between the roles of expert and learner, depending on the language used during each language-related episode.